1996
DOI: 10.1093/oxfordjournals.aje.a008997
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Relation between Smoking and White Blood Cells

Abstract: Higher white blood cell counts in smokers compared with nonsmokers have been well documented, but the longitudinal relation between changes in smoking and changes in white blood cells has not been well described. Since 1984, data have been collected semiannually by the Multicenter AIDS Cohort Study (MACS), a four-center prospective cohort study of acquired immunodeficiency syndrome (AIDS) in homosexual men. The study population includes 2,435 participants who were human immunodeficiency virus (HIV) seronegativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 18 publications
5
63
2
Order By: Relevance
“…Thus it may be speculated that smoking or using other tobacco products may result in similar lowering of lymphocyte percentage. An earlier study had concluded that lymphocytes, especially cytotoxic T cells or CD8+ T cells may get lowered in smokers 25 . Variations in these T lymphocytes may make the smokers vulnerable to develop neoplastic growths and infections 26 .…”
Section: Discussionmentioning
confidence: 96%
“…Thus it may be speculated that smoking or using other tobacco products may result in similar lowering of lymphocyte percentage. An earlier study had concluded that lymphocytes, especially cytotoxic T cells or CD8+ T cells may get lowered in smokers 25 . Variations in these T lymphocytes may make the smokers vulnerable to develop neoplastic growths and infections 26 .…”
Section: Discussionmentioning
confidence: 96%
“…Because cigarette smoking had a strong impact on the risk for developing IFG or Type II diabetes in this study (incident rate of IFG or Type II diabetes mellitus among men with a WBC count of 2.5±5.2´10 9 cells/l: 8.2 per 1000 person-years for non-smokers and 17.2 per 1000 person-years for current smokers), the influence of WBC count on development of IFG or Type II diabetes mellitus might be obscured by cigarette smoking. As for the association of past smoking with WBC count, WBC count is related to the amount of time passed since quitting, and smokers who quit smoking have a reduced WBC count [24,25]. One investigation into the residual effects of smoking on WBC count found that smokers who quit a long time ago had WBC counts more like those who had never used tobacco than those who recently stopped smoking [24] but another study found that long-term ex-smokers still had higher WBC counts than non-smokers [25].…”
Section: Discussionmentioning
confidence: 99%
“…As for the association of past smoking with WBC count, WBC count is related to the amount of time passed since quitting, and smokers who quit smoking have a reduced WBC count [24,25]. One investigation into the residual effects of smoking on WBC count found that smokers who quit a long time ago had WBC counts more like those who had never used tobacco than those who recently stopped smoking [24] but another study found that long-term ex-smokers still had higher WBC counts than non-smokers [25]. Because we could not examine years since quitting smoking among past smokers during follow-up, the relationship between the effects of the decline in WBC count with time [12,13] and indicate that the WBC count is a predictor of IFG or Type II diabetes mellitus because of its association with low-grade inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike total leukocyte count, the associations between leukocyte subpopulations and smoking habits, including the effect of quitting, have not been explored extensively. The studies, mostly conducted in men, which did, reported positive associations between smoking and counts of the leukocyte subpopulations, neutrophils, eosinophils, monocytes, and lymphocytes (2,9,10,16).…”
Section: Introductionmentioning
confidence: 99%
“…The strongest known correlate of the leukocyte count is cigarette smoking, with smokers having higher mean counts than never smokers (1)(2)(3)(4)(5)(6)(10)(11)(12)(13)(14)(15). Some studies reported an increase in leukocyte count with number of cigarettes smoked daily and a decrease after cessation of smoking (9-11, 13, 14).…”
Section: Introductionmentioning
confidence: 99%